2002
DOI: 10.1108/03074350210768068
|View full text |Cite
|
Sign up to set email alerts
|

Measuring productivity changes in Australian banking: an application of Malmquist indices

Abstract: The purpose of this paper is to analyse the change in the productivity of Australian banks during the period 1995 to 1999. Productivity has been measured by the Malmquist index, using a Data Envelopment Analysis (DEA) technique. The data consists of a panel of 17 locally incorporated banks in Australia. The study finds that the technical efficiency of banks in the panel has declined by 3.1 per cent and the Total Factor Productivity (TFP) index declined by 3.5 per cent during 1995-1999. Though the mean technica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0
8

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 21 publications
1
53
0
8
Order By: Relevance
“…The productivity of Gulf corporation council was measured by Ramakrishnan (2007) and only 15 out of 55 banks were rated as efficient banks. Sathye (2002) found a decline in the total factor productivity of Australian bank by 3.5% during the study period of 1995-1999.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The productivity of Gulf corporation council was measured by Ramakrishnan (2007) and only 15 out of 55 banks were rated as efficient banks. Sathye (2002) found a decline in the total factor productivity of Australian bank by 3.5% during the study period of 1995-1999.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are numerous studies which focus their analysis on the bank productivity of different countries. Like, Tina Zhang and Wang (2014) on Chinese banks; Rezitis (2006) and Chatzoglou et al (2010) on Greek banks; Ataullah and Le (2006), Kumar and Gulati (2008), Das (2010), and Kumar and Gulati (2010) for Indian banks; Berger and EJBE 2015, 8 (16) Mester (1999), and Elyasiani and Mehdian (1990) for U. S. banks; Sathye (2002) for Australian banks are some notable studies amongst others. Also, there are studies on profitability analysis of banks by different researchers like Ho and Tripe (2002); Guru et al (2002);DeYoung and Rice (2004); Haung and Chen (2006) and Pasiouras and Kosmidou (2007).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Drake (2001) examined the productivity of British banking sector between 1984 and 1995. Sathye (2002) examined the productivity of 17 banks in Austria's banking system between 1995 and 1995. Vivas and Humphrey (2002) analyzed Spanish banking productivity between 1986 and 2001.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sathye (2002) measured productivity changes in Australian banks by the Malmquist index using DEA technique during the period 1995 to 1999. He concluded that there is a decline in technical efficiency and total productivity factor during the study period and also no correlation was found between size and productivity which is important in the context of bank merger debate in Australia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, caused by compulsory superannuation Australia has the 4th largest pension fund pool in the world which highlights the role of banking industry in this country. Due to this key position, measuring banks and financial institutions' performance is an issue of major interest for academics and policy makers (e.g., Avkiran, 1999Avkiran, , 2000Avkiran, , 2004Kirkwood & Nahm, 2006;Moradi-Motlagh, Saleh, Abdekhodaee, & Ektesabi, 2011;Neal, 2004;Paul & Kourouche, 2008;Sathye, 2001Sathye, , 2002Sturm & Williams, 2004;Walker, 1998;Wu, 2008).…”
Section: Introductionmentioning
confidence: 99%